On set-valued functional integral equations of Hammerstein-Stieltjes type: existence of solutions, continuous dependence, and applications - El-Sayed, A. M. A.; Al-Issa, S. M. (Methods of Functional Analysis and Topology, 2021)
We study the existence of continuous solutions of a nonlinear functional integral inclusion of Hammerstein-Stieltjes type. The continuous dependence of the solutions on the set of selections and on some other functions will be proved. Nonlinear set-valued functional integral equations of Chandrasekhar type and nonlinear set-valued fractional-orders functional integral equations will be given as applications. An initial value problem of fractional-orders set-valued integro-differential equation will be considered. Досліджується існування неперервних розв’язків нелінійного функціонального інтегрального включення типу Гамерштейна-Стілтьєса. Доведена неперервна залежність розв’язку від множини виборок і деяких інших функцій. Як застосування, розглядаються нелінійні багатозначні функціональні інтегральні рівняння типу Чандрасекара і нелінійні багатозначні функціональні інтегральні рівняння дробових порядків, а також задачі з початковими умовами для останнього класу рівнянь.